1984
DOI: 10.1007/bf00683883
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of serum sulph-hydryl groups by hydrogen peroxide secreted by stimulated phagocytic cells in rheumatoid arthritis

Abstract: Levels of free sulph-hydryl (SH) groups are depressed in the sera of patients with rheumatoid arthritis, especially during active disease. However, the mechanism underlying this effect is not known. We have investigated several oxidative species generated during the inflammatory process for their ability to react with serum SH in vitro. Our results show that serum oxidase enzymes (e.g. caeruloplasmin) do not have this activity but that "active oxygen species" generated either by an enzymatic reaction (xanthine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…It is speculated that plasma SH groups act as an important extracellular scavenger of peroxides and are also helpful in protecting the surrounding tissues (Hall et al 1984). Critical SH groups on cell membranes protect proteins against oxidative damage by MPO-derived HOCI (Weiss 1989), while they are consumed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is speculated that plasma SH groups act as an important extracellular scavenger of peroxides and are also helpful in protecting the surrounding tissues (Hall et al 1984). Critical SH groups on cell membranes protect proteins against oxidative damage by MPO-derived HOCI (Weiss 1989), while they are consumed.…”
Section: Discussionmentioning
confidence: 99%
“…Critical SH groups on cell membranes protect proteins against oxidative damage by MPO-derived HOCI (Weiss 1989), while they are consumed. The reduced plasma SH levels have also been attributed to the actions of H2O2 (Hall et al 1984), and transition metal ions (Halliwell and Gutteridge 1990b) promote oxidation of SH groups; further Op is a specific oxidase for SH containing small molecules (Rae et al 1986). In the present study, decreased plasma SH levels were observed in BD patients; and there was a positive correlation between SH and TF levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the number of free SH groups in the sera of rheumatoid arthritis (RA) patients is depressed.1 2 This depression is associated with the activity of the disease.2 Hall et al 3 have shown in vitro that H202 formed during phagocytosis by granulocytes diminishes the amount of free SH groups. These authors propose that serum SH groups act as important extracellular scavengers of peroxides and are therefore helpful in protecting the surrounding tissues.…”
mentioning
confidence: 99%
“…If there is an imbalance, it can result in the formation of reactive oxygen radicals leading to endothelial dysfunction and apoptosis [30,31]. It has been observed that plasma SH groups act as an important extracellular scavenger of peroxides and are also helpful in protecting the surrounding tissues [32]. Critical SH groups on cell membranes protect proteins against oxidative damage by MPO-derived HOCI, while they are consumed [33].…”
Section: Discussionmentioning
confidence: 99%